Transmitted antiretroviral drug resistance and thumb subdomain polymorphisms among newly HIV type 1 diagnosed patients infected with CRF01_AE and CRF07_BC virus in Guangdong Province, China - Yang, Changfu; Liu, Shuyuan; Zhang, Taisong; Hou, Yaping; Liu, Xiaoli; Gao, Yun; Yang, Guang; Wang, Zhen; Chen, Huayun; Li, Ming; Zhu, Zhenyu (AIDS research and human retroviruses, 2012)
The aim of this study was to elucidate the prevalence of transmitted drug-resistant (TDR) mutations and reverse transcriptase (RT) thumb subdomain polymorphisms in CRF01_AE and CRF07_BC virus among newly diagnosed, therapy-naive HIV-1 patients in Guangdong Province, China. One hundred and sixty-four samples were collected in the Guangzhou Eighth People's Hospital. The entire protease gene and 300 codons of the entry part of the reverse transcriptase were amplified and sequenced. Furthermore, genotypic drug resistance, polymorphisms, and their phylogeny were analyzed. According to eligibility criteria, seven samples were excluded, and 119 of 157 (75.8%) samples (84 CRF01_AE and 35 CRF07_BC) were amplified and sequenced successfully. The prevalence of TDR identified in the present study was 6.7% [8/119, 95% confidence interval (CI) 1.8-11.6%]. Three major resistance mutations, K103N, M184V, and Y188L, each of which caused more than one drug resistance, appeared in only two patients; the prevalence [1.7 % (2/119)] was relatively low. Until now, this is the first observation of the five newly identified accessory mutations, V35T, K43E, V60I, K122E, and E203D, and seven thumb subdomain polymorphisms, A272P, K277R, K281R, T286A, E291D, V292I, and I293V, in the RT gene in China. These findings provide useful information for guidance on the antiretroviral therapy (ART) policy in China where therapeutic options are still limited.